Pengaruh Tingkat Suku Bunga Kredit, Jangka Waktu Pinjaman dan Keadaan Ekonomi Terhadap Kredit Bermasalah Pada BUMDES Giri Amertha Sadhu Desa Bontihing - Made Widi Adnyana; I Putu Arya Dharmayasa (Universitas Pendidikan Ganesha, 2025)
The purpose of this study was to examine the effect of credit interest rates, loan terms, and economic conditions on non-performing loans at Giri Amertha Sadhu Village-Owned Enterprises (BUMDES) in Bontihing Village. The study was conducted in Bontihing Village, Kubutambahan District, involving 45 customers as respondents. The sampling technique used was simple saturated. The method used in the data collection process was a questionnaire and analyzed using multiple linear regression. The hypothesis testing process used t and F tests using SPSS 16.0 for windows. The results of the study showed that credit interest rates, loan terms, and economic conditions had a significant influence on non performing loans at Giri Amertha Sadhu Village-Owned Enterprises (BUMDES) in Bontihing Village, each contributing 30% of the credit interest rate, 22.9% of the loan term, and 45% of the economic conditions. And simultaneously influencing 31.4%.